The Influence of Financing Structure on Performance of MSMEs in South African: "The Valley of Death" - Seroka, Ngwanatau (African Inst. of Fin. Markets and Risk Mngnt, 2018)
Previous researchers, especially on large enterprises, have revealed that debt financing structure influences enterprise performance. Though the issue has been extensively researched, micro, small, and medium-sized enterprises (MSMEs) have traditionally been operating differently as compared to large enterprises in terms of their financial decisions, ownership and management style, and behaviour. Therefore, this study will explore the gaps encountered by all MSMEs to grow their businesses. These include forms and type of industry, firm size, asset tangibility, and a firm’s current assets in relation to its current liabilities and profitability level. The study examines the influence of financing structures on performance of micro, small and medium-sized enterprises (MSMEs) in South Africa. The ordinary least squares (OLS) technique of measurement is applied to examine the effects of financing structure on performance across various industrial sectors in the years 2013, 2014 and 2015. The findings in this study indicate an increase in the use of leverage to drive the influence of total debt on performance in all industrial sectors of MSMEs in South Africa. From the cross-sectional regression analysis, the results show that financing structure has a negative effect on the profitability of MSMEs, although not absolutely. The findings show that the size of the enterprise, asset tangibility, and the ratio of current assets to current liabilities are the most influential of borrowing decisions in total debt, short-term debt, and long-term debt. A significantly negative effect is observed for long-term debt, while short-term debt (STDR) exhibits a significantly positive effect. Thus the influence on MSMEs’ leverage on performance is driven by the usage of short-term debt. The variables of size of the firm, and ratio of current assets to current liabilities, do not have the same effect in all debt levels; the significance is substantially higher for long-term debt than for total debt and short-term debt. On the other hand, our empirical results suggested that transactional costs, and an asymmetric information problem in smaller firms, may lead to a mainly negative influence on size and total debt. The asset structure on profitability observed across the years showed mixed experiences. The ratio of current assets to current liabilities was found to be positive and significant on long-term debt and short-term debt leverage.